Does Your School Have the Maker Fever? An Experiential Learning Approach to Developing Maker Competencies (LEARNing Landscapes, 2018)
The maker movement in education is linked to better, more authentic learning that can help students develop 21st century competencies. Maker experiences, like any experiential learning, can be limited by decontextualized, recipe-style labs and fail to deliver on the promise of engaged learners ready to learn on demand and solve the ill-defined problems of the 21st century. Our multiphase research program on maker culture in education held a series of exploratory workshops and social events to discover the competencies required to turn experiential learning with technology into maker experiences that meet 21st century needs.
Keywords: maker culture; experiential learning; 21st century competencies